EFFECTIVENESS OF LAVENDER AROMATHERAPY INHALATION AND MUROTTAL MUSIC REDUCE ANXIETY IN PRIMIPAROUS MOTHERS - Puput Kurnia Sari; Sri Yunita Suraida Salat; Eka Meiri Kurniati; Yulia Wardita (Universitas Karya Husada Semarang, 2026)
Background:The postpartum period is a phase of physical and psychological adaptation that may trigger anxiety, particularly among primiparous mothers who are experiencing motherhood for the first time. Untreated anxiety can negatively affect maternal recovery, sleep quality, breast milk production, and mother–infant bonding. Non-pharmacological interventions such as lavender aromatherapy inhalation and murottal music have been reported to provide relaxation effects and reduce anxiety levels.ThepurposeofthisstudywastoTo determine the effectiveness of lavender aromatherapy inhalation and murottal music in reducing anxiety levels among primiparous postpartum mothers.Thisresearch method wasquantitativeresearch,quasi-experimental design withtwogrouppre andpost testdesign, the studypopulation wasall primiparouspostpartum mothers at Tuntang Health Center in Februari 2026. A sample of15the lavender aromatherapy inhalation and 15the murottal music respondents. The results of this study There a significant difference in effectiveness between the two interventions (p-value = 0.021), with lavender aromatherapy demonstrating greater effectiveness in reducing anxiety levels. TheconclusionofthetwointerventionsthatisBoth lavender aromatherapy inhalation and murottal music effectively reduced anxiety levels postpartum mothers. Lavender aromatherapy demonstrated greater effectiveness compared to murottal music.